Modern Trends in Teaching Russian Language in Primary Education - Tokhta Ametovna Yuldasheva (Euro Asian Journal Publishing, 2024)
This article is devoted to the study of modern trends in teaching the Russian language in primary school. An analysis of scientists' research in the field of teaching the Russian language to children of primary school age was carried out. Methods and forms of teaching are presented that contribute to the activation of cognitive activity of younger schoolchildren. Conclusions are drawn about the advisability of using extracurricular activities in the process of teaching the Russian language in primary school.
Keywords: Russian language, primary school, extracurricular activities, spelling, activation of learning, methods of studying spelling